Visualization of Flagella during Bacterial Swarming - Turner, Linda (American Society for Microbiology (ASM), 2010)
When cells of Escherichia coli are grown in broth and suspended at low density in a motility medium, they swim independently, exploring a homogeneous, isotropic environment. Cell trajectories and the way in which these trajectories are determined by flagellar dynamics are well understood. When cells are grown in a rich medium on agar instead, they elongate, produce more flagella, and swarm. They move in coordinated packs within a thin film of fluid, in intimate contact with one another and with two fixed surfaces, a surfactant monolayer above and an agar matrix below: they move in an inhomogeneous, anisotropic environment. Here we examine swarm-cell trajectories and ways in which these trajectories are determined by flagellar motion, visualizing the cell bodies by phase-contrast microscopy and the flagellar filaments by fluorescence microscopy. We distinguish four kinds of tracks, defining stalls, reversals, lateral movement, and forward movement. When cells are stalled at the edge of a colony, they extend their flagellar filaments outwards, moving fluid over the virgin agar; when cells reverse, changes in filament chirality play a crucial role; when cells move laterally, they are pushed sideways by adjacent cells; and when cells move forward, they are pushed by flagellar bundles in the same way as when they are swimming in bulk aqueous media. These maneuvers are described in this report.